2018
DOI: 10.1111/gtc.12591
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR‐140‐3p in Wnt3a and TGFβ3 signaling pathways during osteoblast differentiation in MC3T3‐E1 cells

Abstract: The Wnt/β-catenin signaling and TGFβ signaling pathways play a key role in osteoblast differentiation. The miRNAs play important roles in regulating gene expression at the post-transcriptional level through fine-tuning of protein-encoding gene expression. However, involvement of miRNAs is not established for Wnt3a and TGFβ signaling pathways in osteoblast differentiation. Here, we examined the role of miRNAs expressed differentially after Wnt3a expression during osteoblast differentiation. Over-expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…It suggested that TGF-β3 may regulated by miR-140-5p in multiple ways, including Smad3 pathway. Novel evidences demonstrating that miR-140-3p negatively controlled TGF-β3, which proved to be a direct target of miR-140-3p (Fushimi et al, 2018). That’s may explained why co-transfection of miR-140-5p mimics and Si-Smad3 showed a lower expression of TGF-β3.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that TGF-β3 may regulated by miR-140-5p in multiple ways, including Smad3 pathway. Novel evidences demonstrating that miR-140-3p negatively controlled TGF-β3, which proved to be a direct target of miR-140-3p (Fushimi et al, 2018). That’s may explained why co-transfection of miR-140-5p mimics and Si-Smad3 showed a lower expression of TGF-β3.…”
Section: Discussionmentioning
confidence: 99%
“…However, when overexpressed, miR-140-3p stimulated the transcription of OCN in MC3T3-E1 cells. Thus, miR-140-3p regulated osteoblast differentiation by acting as a regulatory factor between Wnt3a and TGFβ3 signaling pathways [92]. According to the study, miR-133a-5p overexpression was shown to significantly lower the expression of osteoblast differentiation markers as well as ECM mineralization in MC3T3-E1 cells by targeting 3 UTR of Runx2 and reduce Runx2 expression at both mRNA and protein levels [93].…”
Section: Mirnas Involved In Osteoblast Regulationmentioning
confidence: 98%
“…It is worth mentioning that four of the miRNAs (miR‐140‐3p, miR‐148a, mir‐218, and miR‐214), previously discussed in the context of fracture repair, are also listed as involved in bone remodeling. For example, miR‐140‐3p was found in osteoblast‐derived exosomes and in osteoblastic MC3T3 cells and has been shown to promote osteoblast differentiation . Additionally, miR‐148a and miR‐218 were found in osteoblast precursor exosomes and in human BMSCs where the former promotes osteoclastogenesis and the latter enhances osteoblast differentiation .…”
Section: Mirnas In Exosomesmentioning
confidence: 99%
“…For example, miR-140-3p was found in osteoblast-derived exosomes and in osteoblastic MC3T3 cells and has been shown to promote osteoblast differentiation. (67) Additionally, miR-148a and miR-218 were found in osteoblast precursor exosomes and in human BMSCs where the former promotes osteoclastogenesis (68) and the latter enhances osteoblast differentiation. (69) Lastly, miR-214-3p is found in osteoclast-derived exosomes and inhibits osteoblastic bone formation ( Figure 4).…”
Section: ↑Mir-148bmentioning
confidence: 99%
See 1 more Smart Citation